Concurrent simulation in the cloud with the mJADES framework. (1st January 2013) - Cuomo, Antonio; Rak, Massimiliano; Villano, Umberto
In this paper, we discuss the design and implementation of mJADES, a new simulation engine that runs on top of an ad-hoc federation of cloud providers and is designed to perform multiple concurrent simulations. These features make mJADES an attractive environment for the simulation of complex systems, in which it is often desirable to perform many simulation runs, either for statistical validation or to compare the system behaviour in several different conditions. Given a set of simulation tasks, mJADES is able automatically to acquire the computing resources needed from the cloud, and to distribute the simulation runs to be executed.